ANALISIS KUALITAS PELAYANAN DAN PARTISIPASI ANGGOTA KOPERASI PADA KOPERASI WANITA NURUL AMAL KOTA PEKANBARU - Asria, Doni; Syakdanur, Syakdanur; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Cooperative task is none other than the body tasked to provide services (service) to its members as cheaply as possible, as smoothly as possible and as best as possible, and able to provide a quality service to the needs of its members. Members have a very important role in the cooperative, since cooperatives can only live, grow and develop if it gets the support of its members, namely those who are aware of the membership, to know their rights and obligations and is able and willing to follow the rules of the game in a cooperative organization. This study aimed to determine the quality of service and level of member participation as owners and customers on Women's Cooperative Nurul Amal Pekanbaru. The study began with prariset in March 2015. The population in this study are members of the cooperative who has been a member of the cooperative for 5 years amounted to 130 people using pursosive sampling techniques, the samples obtained as many as 56 people. The data collection technique used was a questionnaire, then the data is analyzed. The results showed that the five dimensions of quality of service cooperatives showed that overall has a good quality. While the results of the study included the participation of members of the cooperative being. Based on the results of this study concluded that service quality Nurul Amal Women's Cooperative Pekanbaru City are in good category and the participation of members of Nurul Amal Women's Cooperative Pekanbaru in middle category. To improve the quality of service of the cooperative board is expected to consider the condition of the building cooperative and look for employees to schedule a cooperative operations run as specified. Furthermore, to increase the participation of members, administrators need to increase knowledge of the cooperative and the need for traction in following the annual meeting of members. Besides the need for traction in Waserda cooperative shop.Keywords: Services Quality, Members Participation